Community asthma clinics: 1993 survey of primary care by the National Asthma Task Force. Issue 3 (September 1994) - Barnes, G; Partridge, M R
Abstract : OBJECTIVES–To establish a baseline of work done in primary care asthma clinics in the United Kingdom and to assess the degree of clinical delegation to nurses and the appropriateness of their training. DESIGN–Prospective questionnaire survey of asthma care in general practices and a subsidiary survey of all family health services authorities (FHSAs) of the number of asthma clinics in their area. SETTING–All 14, 251 general practices in the United Kingdom and 117 FHSAs or health boards (Scotland and Northern Ireland). RESULTS–Questionnaires were returned by 4327 (30.4%) general practices, 54% being completed by practice nurses and 22% by general practitioners; in 24% profession was not stated. In all, 77.2% (3339/4327) of respondents ran an asthma clinic. 60 FHSAs state the number of asthma clinics at the time of the general practice survey (total 3653 clinics); within responding FHSAs 1702 (46.6%) practices running an asthma clinic replied to the general practice survey. Clinics exclusive for patients with asthma mostly occurred in practices with five or more general practitioners (70.2%), compared with single-handed practices (31.7%). The average number of asthma clinics run per practice was five a month; the average duration was 2 hours and 20 minutes. 1131 (48.8%) nurses ran clinics by themselves, 1180 (47.9%) with the doctor, and 39 (1.7%) had no medical input. Comprehensive questioning occurred other than for nasal (872, 26.1%) or oesophageal (335, 10.0%) symptoms and use of aspirin and non-steroidal drugs (1161, 33.4%). Growth in children was measured by only a third of respondents. Of the 1131 nurses who ran clinics alone, 251 (22.2%) did so without formal training entailing assessment. CONCLUSION–Asthma clinics are now common in general practice and much of their work is done by nurses, a significant minority of whom may not have had sufficient training. IMPLICATIONS–As this survey is probably biased toward the more asthma aware practices, greater deficiencies in training and standards may exist in other practices. Further evaluation of the effectiveness of asthma clinics is needed.